Magnetic Field of a Compact Spherical Star under f(R, T) Gravity. (September 2018) - Islam, Safiqul; Basu, Shantanu
Abstract : We present the interior solutions of distributions of magnetized fluid inside a sphere in f(R, T) gravity. The magnetized sphere is embedded in an exterior Reissner–Nordström metric. We assume that all physical quantities are in static equilibrium. The perfect fluid matter is studied under a particular form of the Lagrangian density f(R, T). The magnetic field profile in modified gravity is calculated. Observational data of neutron stars are used to plot suitable models of magnetized compact objects. We reveal the effect of f(R, T) gravity on the magnetic field profile, with application to neutron stars, especially highly magnetized neutron stars found in x-ray pulsar systems. Finally, the effective potential V eff and innermost stable circular orbits, arising out of the motion of a test particle of negligible mass influenced by attraction or repulsion from the massive center, are discussed .